The scope, merits and limitations of Tannen's Theory of the nature of the relationship between orality and literacy [microform] - Von Gruenewaldt, Judith Theresa (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil) -- University of Stellenbosch, 1998.